2023
DOI: 10.4209/aaqr.220252
|View full text |Cite
|
Sign up to set email alerts
|

Inter-laboratory Comparison between Particle and Bacterial Filtration Efficiencies of Medical Face Masks in the COVID-19 Context

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) transmission lead to the recommendation of mask wearing during the pandemic COVID -19. Bacterial filtration efficiency (BFE) measurements are used to measure the efficiency of medical face masks in preventing the spread of bioaerosols. Even though these measurements are simple, BFE testing still raise several scientific questions. This paper presents an inter-laboratory comparison between Bacterial Filtration Efficiency (BFE) and Particle Filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Each sample is conditioned at a temperature of 21 ± 5 °C and a relative humidity of 85 ± 5% for at least 4 hours to achieve atmospheric equilibrium before testing. 29…”
Section: Bfe Testing Protocolmentioning
confidence: 99%
“…Each sample is conditioned at a temperature of 21 ± 5 °C and a relative humidity of 85 ± 5% for at least 4 hours to achieve atmospheric equilibrium before testing. 29…”
Section: Bfe Testing Protocolmentioning
confidence: 99%
“…Also, the relative pressure drops measured were found in the three-test to be comparable to or lower than the limit value required for the FFP3 (~3.0 mbar), thus indicating that a low air flow resistance occurs in the fabric, making breathing comfortable for the wearers. Several studies reported that a positive correlation occurs between BFE and PFE, and a slight difference observed in the assessment of the filtration performance of face masks between these two methods is mainly due to the utilization of a different aerosol size distribution [87,96,97]. The aerosol generated for the PFE test is composed of monodisperse particles, which are characterized by a diameter of ~0.6 µm.…”
Section: Filtration Performancementioning
confidence: 99%
“…Unlike PFE protocol, the mean particle size of ~3.0 µm imposed by the BFE method is obtained as an average estimate of the total count of the six stages of the aerosol cascade impactor, which is characterized by a wide granulometric range of 0.6-7 µm. Since all particles within this range are considered in the estimation of the BFE, a transmission of particles with sizes below 3.0 µm, even if they are a small amount of the total generated aerosol, through the tested filter can create a significant decrease in the BFE [96,97]. It is important to note that the value of BFE measured for the PVDF-HFP membrane was equal at least to ~99%, thus indicating a constant filtration through all the granulometric range, and also for particles smaller than 3.0 µm.…”
Section: Filtration Performancementioning
confidence: 99%